2019
DOI: 10.29356/jmcs.v62i4.679
|View full text |Cite
|
Sign up to set email alerts
|

Refractometric study on binary, ternary, and quaternary solutions made by water, methanol, ethanol, glycerol, D-glucose monohydrate (DGMH), sucrose, and sodium chloride at T = 293.15 K and atmospheric pressure

Abstract: The glycerol, D-glucose monohydrate (DGMH), sucrose, and sodium chloride are used in food industries and the measurement of properties for these components and their aqueous solutions can be important. In this research work, the refractive indices for binary solutions of (methanol + glycerol), (ethanol + glycerol), ternary solutions of (water + glycerol + DGMH), (water + glycerol + sucrose), (water + sucrose + DGMH), (water + sucrose + ethanol), (water + ethanol + DGMH), (water + NaCl + DGMH), (water + methano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 32 publications
(35 reference statements)
1
5
0
Order By: Relevance
“…We cannot, however, compare the interaction parameters obtained from our analysis to the excess molar refractivity as the two physical parameters depend on different properties of the medium, but it validates that our model can successfully predict the positive and negative deviation from ideality. This observation can be validated from previous thermodynamic studies also. So, our proposed model of ThT quantum yield can successfully estimate the degree of solvent–solvent interaction and can predict nonideality without any help from excess thermodynamic property measurements.…”
Section: Resultssupporting
confidence: 69%
See 4 more Smart Citations
“…We cannot, however, compare the interaction parameters obtained from our analysis to the excess molar refractivity as the two physical parameters depend on different properties of the medium, but it validates that our model can successfully predict the positive and negative deviation from ideality. This observation can be validated from previous thermodynamic studies also. So, our proposed model of ThT quantum yield can successfully estimate the degree of solvent–solvent interaction and can predict nonideality without any help from excess thermodynamic property measurements.…”
Section: Resultssupporting
confidence: 69%
“…The refractive index values of exact compositions of the methanol–glycerol solvent mixture used in this study at 25 °C are reported in the literature . For ethanol–glycerol, n -butanol–glycerol, and tert -butanol–glycerol mixtures, the refractive index values are reported in several compositions but not at the exact compositions of the mixtures prepared by us. To estimate the values at our experimental compositions, we fitted the reported data using a second-order polynomial equation and evaluated the required values from it. The literature values along with the estimated refractive indexes are reported in Supporting Information Table S2.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations